A Comprehensive Analysis of Various Teaching Strategies and Innovations at Higher Education Level - Mittal, Alka; Agarwal, Neeru Mohini (JOURNAL OF INDIAN EDUCATION, 2009)
Teaching strategy helps the teacher to establish interaction between him and his students and the curriculum or subject matter. The selection of effective strategies of teaching in different streams of education at higher level is a challenge of modern time. We are experiencing massive changes in the form of globalisation, liberalisation and privatization. In this situation our learners have face a great challenge for their future. Therefore, a teacher has a great responsibility to change the situation. First of all he/she should adopt permissive style of strategies such as heuristics, project strategy, review, group discussion, paper presentation, independent study, computer assisted instruction, etc. for making our teaching effective, so that students can move back towards their classrooms. In order to make his/her teaching effective, they can use various strategies and innovations to modify their teaching. Some of them are related with ICT and some are without ICT. Strategies such as workshop, conference, seminar, panel discussion, symposium, informal group plan, various co-operative learning techniques such as Jigsaw, think-pair-share, threestep interview, round table, group investigation, student teams achievement division, round robin brain storming, three-minute review, etc. can be used successfully without ICT in order to change teaching-learning process. On the other hand, due to vital role of ICT in present scenario of globalisation and liberalisation, the teacher can take the help of ICT for teaching. The new communication and information technologies have profoundly affected our social structure. There is a growing interdependence between technology, information and society. The use of communication technologies in education at higher level has been identified. The computing and telecommunication technologies are enabling the teacher to develop multimedia in which text, voice, pictures, simulation, etc. can be integrated and delivered through computers as an interactive learning package. To compete and survive in the competitive world of higher education it is essential for teachers to create, adopt and utilize new technologies for higher education. With the use of above strategies either with ICT or without ICT a teacher can innovate his teaching method according to need of society. And with this, higher education of India will cross the country’s border and will change the world into a ‘global village’.